IMPLEMENTASI SANKSI PERJUDIAN SABUNG MANUK MENURUT QANUN NO 6 TAHUN 2014 TENTANG HUKUM JINAYAT - Yulanda Sari; Ida Friatna; Nurul Fithria (Journal of Indonesian Comparative of Syari'ah Law, 2025)
Qanun is a form of regional legislation that applies specifically in the Aceh Province, as part of the region’s special autonomy and privileges in implementing Islamic Sharia values. This is regulated under Law Number 11 of 2006 concerning the Governance of Aceh. One of the significant regulations born from this authority is Qanun Number 6 of 2014 on Jinayat Law, which prohibits jarimah maisir or all forms of gambling, including cockfighting practices. Cockfighting is an activity where two roosters are pitted against each other for the purpose of entertainment and betting. Although some communities consider it a tradition or a form of amusement, the practice involves elements of gambling due to the presence of money or valuables being wagered. Therefore, cockfighting falls under the category of maisir and is legally prohibited. Beyond violating the law, cockfighting has negative impacts on public order, lowers the moral standards of the younger generation, and contradicts Islamic values that prohibit gambling and cruelty to animals. Field observations, such as those in Tangga Besi Village, Simpang Kiri Subdistrict, Subulussalam City, show that cockfighting is still widely practiced by the community. These activities are often conducted secretly in remote locations that are difficult for law enforcement to access. Several factors contribute to the persistence of this practice, including poor economic conditions, a lack of religious understanding, environmental influences, and deeply rooted cultural habits. Although law enforcement efforts have been carried out by the Satpol PP and Wilayatul Hisbah, the results remain less than optimal. Therefore, eradicating cockfighting requires synergy between law enforcement officials, religious leaders, the community, and village authorities to build legal awareness and create an environment more aligned with the principles of Islamic Syariat.